An Analysis on the Lecturers’ Mispronunciation of Common Words Used at the English Language Program - Zulfa, Riang Permata; Wati, Laila; Maysuroh, Siti (Universitas Hamzanwadi, 2018)
This research aimed at knowing the lecturers’ mispronunciation of common words used in the English Language Education Program of Hamzanwadi University and to analyze the factors cause them do mispronunciation. The research questions were formulated as: (1) What are the mispronunciation of the lecturers at the English Language Education Program in Hamzanwadi University?, (2) What are the factors of the mispronunciation made by the lecturers at the English Language Education Program in Hamzanwadi University? To achieve the purpose of the research and answer the research problem, the present researcher interview 6 out of 18 lecturers and gave them an oral test. The collected data were submitted to descriptive analysis. The result of the study discovered that all of the participants do mispronunciation in most common words proposed. The finding of the study implies that the factors of this mispronunciation are; (1) mother tongue influence, (2) effect of personality, (3) different accent, (4) word stress position. In short, the all factors that cause mispronunciation refer to the different language between the L1 and the target language.